Analysis of water resource ecological optimization and obstacles based on the water resources – socio – economic – ecological environment model framework – a case study of the core area of the Central Plains urban agglomeration - Li, Jinhang; Zhao, Mengdie; Han, Yuping; Wei, Jinhai (Frontiers in Ecology and Evolution, 2023)
The ecological health level of water resources plays a crucial role in achieving sustainable development in society. This study focuses on the core area of the Central Plains urban agglomeration, selecting 14 cities as the research subjects. A comprehensive evaluation system, based on the Water Resources - Socio-Economic - Ecological Environment model framework, was constructed, incorporating 22 evaluation indicators in the indicator layer. Using an improved entropy weighting method combined with the ITOPSIS model, the water ecological health level in the study area from 2013 to 2022 was evaluated, and corresponding measures were proposed based on the evaluation results. Furthermore, the Barrier Degree model was applied to identify the eight major hindering factors influencing the water resource ecological environment in the research area. The findings of this study provide a theoretical basis for enhancing the water ecological health level in urban agglomerations worldwide.